2017
DOI: 10.1038/s41598-017-17438-3
|View full text |Cite
|
Sign up to set email alerts
|

Full-scale experimental investigation of deposition and corrosion of pre-protector and 3rd superheater in a waste incineration plant

Abstract: Municipal solid waste (MSW) incineration is widely adopted as a waste management strategy and for the energy production. However, this technology experience grave deposition and corrosion of the boiler tubes due to high chlorine (~1.09wt.%) and alkali metal (Na, K) content in MSW. Little is known about the concentration profile of these corrosive elements in the deposits at different boiler locations. Therefore, a full-scale experimental investigation was conducted to determine the concentration profile of Cl,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The eutectics mentioned above in the existed liquid form prevent the formation of a compact protective layer of corrosion products and at the same time create a precondition for the course of electrochemical corrosion because the liquid phase is an electrolyte [ 24 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The eutectics mentioned above in the existed liquid form prevent the formation of a compact protective layer of corrosion products and at the same time create a precondition for the course of electrochemical corrosion because the liquid phase is an electrolyte [ 24 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hansen et al [8] reported that an inner layer of KCl was the species deposited first and then reacted with gaseous SO 2 /SO 3 to form K 2 SO 4 . In contrast, Ma et al [9] found that alkali sulfates were the initial deposit layers and alkali chlorides were more distributed in outer layers. As for corrosion, the problem of how Cl penetrates the oxide film in the "active oxidation" mechanism remains to be solved [10].…”
Section: Introductionmentioning
confidence: 88%
“…When the temperatures reach 600 o C, these species are discharged into the flue gas as HCl, KCl, K2SO4, and KOH, which can exacerbate the production of ash deposits and corrosion issues on the IOP Publishing doi:10.1088/1755-1315/1201/1/012001 2 heated metal surface [4]. The investigation conducted by Ma et al [5] Analyzed the deposits at the superheater and pre-protector Waste to Energy (WtE) plant and found abundant Cl, K, and Na content, which resulted in damage due to corrosion attack.…”
Section: Introductionmentioning
confidence: 99%